Developing the rapidkuantan system to reduce idle time among the stations using simulation model - Mohammad Samir, Abu Bakar (2016)
This research focus on the route of public transportation from Kuantan to Gambang (UMP). The research aim to reduce time taken by Rapid bus from one stop to another stop. Currently, there are quite number of stops in between these two destination. Yet, some of the stop are close with each other. Thus, it increased the total time of the route. By using the simulation software, this study try to reduce the route time from Kuantan to Gambang by eliminating certain stops which is economically less.